Televisual nostalgia and segment-based shows: evaluating audiovisual archives - Franganillo, Jorge; Guallar, Javier (Anuario ThinkEPI, 2022)
This paper examines segment-based shows and televisual nostalgia from the perspective of audiovisual documentation. Both phenomena have gained prominence in recent years among entertainment shows and represent a firm commitment to the increase in value of audiovisual archives. Segment-based shows are proposed as a curated audiovisual product. However, within this context of documentary product creation, there is concern that press archives, when compared with television archives, are facing a difficult future.
Keywords: Audiovisual archives; Television; Archive montages; Televisual nostalgia; Segment-based shows; Clip shows; Documentary products; Audiovisual documentation; Audiovisual curation